2021
DOI: 10.3390/admsci11040129
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Skills and Aptitudes as Drivers of Organizational Resilience: An Italian Case Study

Abstract: The economic system has experienced heavy consequences caused by the recent pandemic. This paper investigates the interaction between the crisis and organization reaction, focusing on the female managerial role and contribution to overcoming the crisis in male-owned and managed companies. To achieve the research objectives, we used a qualitative research method based on an explorative case study. The results show that female managerial skills have fostered organizational resilience in terms of: (i) the attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Similarly, the findings are in line with Vasilić et al. (2020) and Cosentino and Paoloni (2021) who showed that female managers contribute significantly toward enhancing the resilience capacity of companies. Female employees may do so comfortably, by changing attitudes, promoting new initiatives, building and nurturing formal relationships or by introducing innovating strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the findings are in line with Vasilić et al. (2020) and Cosentino and Paoloni (2021) who showed that female managers contribute significantly toward enhancing the resilience capacity of companies. Female employees may do so comfortably, by changing attitudes, promoting new initiatives, building and nurturing formal relationships or by introducing innovating strategies.…”
Section: Discussionsupporting
confidence: 90%
“…Entrepreneurial resilience and an individual’s self-efficacy support one another to affect the behavior and decision-making of an entrepreneur, particularly in turbulent times (Castro and Zermeño 2020 ; Chen et al 1998 ; Sharma and Rautela 2022 ). Also worthy of consideration are the possible influences on resilience exercised by women holding top management positions (Casprini et al 2022 ; Cosentino and Paoloni 2021 ; Torchia et al 2018 ) and company size. However, there are conflicting positions among scholars about this (Salavou et al 2004 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizations can develop and improve supply chain resilience by creating a risk management culture by increasing employee risk awareness and conducting regular risk assessment exercises [43]. Female executives can achieve change, facilitate new initiatives, solidify and manage formal relationships, and promote resilience [20]. Executive competencies promote resilience by dealing with uncertainty and building relationships, such as entrepreneurial ability, charismatic leadership, transformational leadership, and employee self-efficacy can help companies get out of trouble as soon as possible, adaptive culture is positively correlated with corporate resilience [12,49,54,80].…”
Section: Literature Review 21 Review Of Resilience Researchmentioning
confidence: 99%